2018
DOI: 10.1002/lt.25057
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygosity for the alpha‐1‐antitrypsin Z allele in cirrhosis is associated with more advanced disease

Abstract: Alpha‐1‐antitrypsin deficiency (A1ATD) due to homozygosity for the Z allele (ZZ) is an established risk factor for cirrhosis, but the liver disease risk in heterozygous Z allele carriers (MZ) is controversial. The aim of the present study was to determine the prevalence of the MZ genotype among patients with cirrhosis and the associated risk of decompensation and liver transplantation/mortality. An unselected cohort of 561 patients with cirrhosis and 248 deceased liver donors were genotyped for the A1ATD risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 24 publications
5
62
2
Order By: Relevance
“…In summary, our data and the findings of Schaefer et al suggest A1AT heterozygosity is underdiagnosed despite routine serum A1AT testing. It can be an important cofactor in advanced liver disease and also raises implications for screening of family members.…”
Section: Patients With A1at Deficiency Diagnosed Prior To Lt Comparedsupporting
confidence: 64%
See 3 more Smart Citations
“…In summary, our data and the findings of Schaefer et al suggest A1AT heterozygosity is underdiagnosed despite routine serum A1AT testing. It can be an important cofactor in advanced liver disease and also raises implications for screening of family members.…”
Section: Patients With A1at Deficiency Diagnosed Prior To Lt Comparedsupporting
confidence: 64%
“…The findings of Schaefer et al are supported by our retrospective review of patients undergoing liver transplantation (LT) between 2000 and 2016 at a major Australian center. Explanted livers from 823 patients were assessed to identify patients with histologic evidence of A1ATD (presence of periodic acid–Schiff–positive, diastase‐resistant hepatocyte inclusions and A1AT‐positive immunohistochemistry).…”
Section: Patients With A1at Deficiency Diagnosed Prior To Lt Comparedmentioning
confidence: 82%
See 2 more Smart Citations
“…In our study cohort of 378 patients, the positive predictive value of serum A1AT in patients with a serum concentration of A1AT ≤137 mg/dL was 43.2%. (1) As shown in Fig. 1, a receiver operating characteristic (ROC) curve analysis of the diagnostic performance of A1AT serum concentration in an extended cohort of 4682 patients from our center with an available A1AT phenotype showed that the optimal cutoff to predict heterozygosity for the Z allele was ≤112 mg/dL ( Table 1).…”
Section: To the Editormentioning
confidence: 95%